Susceptibility of European freshwater fish to climate change: Species profiling based on life-history and environmental characteristics - Jarić, Ivan; Lennox, Robert J; Kalinkat, Gregor; Cvijanović, Gorčin; Radinger, Johannes (Global change biology, 2019)
Climate change is expected to strongly affect freshwater fish communities. Combined with other anthropogenic drivers, the impacts may alter species spatio-temporal distributions and contribute to population declines and local extinctions. To provide timely management and conservation of fishes, it is relevant to identify species that will be most impacted by climate change and those that will be resilient. Species traits are considered a promising source of information on characteristics that influence resilience to various environmental conditions and impacts. To this end, we collated life-history traits and climatic niches of 443 European freshwater fish species and compared those identified as susceptible to climate change to those that are considered to be resilient. Significant differences were observed between the two groups in their distribution, life history, and climatic niche, with climate-change-susceptible species being distributed within the Mediterranean region, and being characterized by greater threat levels, lesser commercial relevance, lower vulnerability to fishing, smaller body and range size, and warmer thermal envelopes. Based on our results, we establish a list of species of highest priority for further research and monitoring regarding climate-change susceptibility within Europe. The presented approach represents a promising tool to efficiently assess large groups of species regarding their susceptibility to climate change and other threats, and to identify research and management priorities.
Keywords: Fresh Water; Climate Change; IUCN; ekosystém; Red List; Europe; zvláštnosti životní historie; climate change; Evropa; extinction threat; sladká voda; klimatické změny; global warming; zvířata; Life History Traits; Fishes; ryby; Ecosystem; Animals